2022
DOI: 10.1177/10888683221087527
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating Belief in Free Will and Its Downstream Consequences: A Meta-Analysis

Abstract: Ever since some scientists and popular media put forward the idea that free will is an illusion, the question has risen what would happen if people stopped believing in free will. Psychological research has investigated this question by testing the consequences of experimentally weakening people’s free will beliefs. The results of these investigations have been mixed, with successful experiments and unsuccessful replications. This raises two fundamental questions: Can free will beliefs be manipulated, and do s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 126 publications
2
12
0
Order By: Relevance
“…This finding rules out the possibility that we did not replicate previous findings because the manipulation had no impact on participants' beliefs. Moreover, this result is in line with a current meta‐analysis (Genschow et al, in press) showing that in comparison to other validated experimental free will belief manipulations, the manipulation we chose here produces the strongest effects.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This finding rules out the possibility that we did not replicate previous findings because the manipulation had no impact on participants' beliefs. Moreover, this result is in line with a current meta‐analysis (Genschow et al, in press) showing that in comparison to other validated experimental free will belief manipulations, the manipulation we chose here produces the strongest effects.…”
Section: Discussionsupporting
confidence: 85%
“…Fifth, it could be that free will beliefs are related with cognitive control, but the applied free will belief manipulation was not suited for this purpose. Although we selected the manipulation that produces the strongest effects, a recent meta‐analysis (Genschow et al, in press) indicates that typical free will belief manipulations produce rather unspecific effects in the sense that they not only influence belief in free will, but also other beliefs such as the belief in dualism. In this research, we tested whether our free will belief manipulation influences other factors and found that it does influence belief in free will, but not fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…A current meta-analysis (Genschow et al, 2022) supports this interpretation. Although the meta-analysis found that common anti-free will manipulations reliably reduce beliefs related to free will, it also demonstrated that these manipulations do not affect social behavior.…”
Section: Relation To Social Behaviormentioning
confidence: 52%
“…Strikingly, Baumeister et al’s findings have never been replicated. Since recent research casts doubt on the general link between free will beliefs and social behavior (e.g., Genschow et al, 2022), it is unclear whether Baumeister et al’s findings would withstand a high-powered conceptual replication. Moreover, as Baumeister et al did not control for beliefs other than free will, it remains open whether belief in free will or other beliefs surrounding free will better predict helping behavior.…”
mentioning
confidence: 99%
“…Frequent objects of theorizing in philosophy of mind and philosophy of cognitive science, such as ego depletion (Hagger et al, 2016) or backfire effect (Wood & Porter, 2019) fail to replicate. An extensive meta-analysis appears to undermine previous claims that manipulating free will beliefs is associated with anti-social behavior, such as cheating (Genschow et al, 2022). The implicit association test, a keystone of philosophical theorizing across ethics, metaphysics, and philosophy of mind faces a series of challenges regarding construct validity or usefulness (Buckwalter, 2019;Forscher et al, 2019;Machery, 2022).…”
Section: Philosophy In the Age Of Replication Crisis Sciencementioning
confidence: 96%